Characterization of cold sensitivity and thermal preference using an operant orofacial assay - Caudle Robert M; Vierck Charles J; Rossi Heather L; Neubert John K (SAGE Publishing, 2006)
Abstract Background A hallmark of many orofacial pain disorders is cold sensitivity, but relative to heat-related pain, mechanisms of cold perception and the development of cold allodynia are not clearly understood. Molecular mediators of cold sensation such as TRPM8 have been recently identified and characterized using in vitro studies. In this study we characterized operant behavior with respect to individually presented cold stimuli (24, 10, 2, and -4°C) and in a thermal preference task where rats chose between -4 and 48°C stimulation. We also evaluated the effects of menthol, a TRPM8 agonist, on operant responses to cold stimulation (24, 10, and -4°C). Male and female rats were trained to drink sweetened milk while pressing their shaved faces against a thermode. This presents a conflict paradigm between milk reward and thermal stimulation. Results We demonstrated that the cold stimulus response function was modest compared to heat. There was a significant effect of temperature on facial (stimulus) contacts, the ratio of licking contacts to stimulus contacts, and the stimulus duration/contact ratio. Males and females differed only in their facial contacts at 10°C. In the preference task, males preferred 48°C to -4°C, despite the fact that 48°C and -4°C were equally painful as based on their reward/stimulus and duration/contact ratios. We were able to induce hypersensitivity to cold using menthol at 10°C, but not at 24 or -4°C. Conclusion Our results indicate a strong role for an affective component in processing of cold stimuli, more so than for heat, which is in concordance with human psychophysical findings. The induction of allodynia with menthol provides a model for cold allodynia. This study provides the basis for future studies involving orofacial pain and analgesics, and is translatable to the human experience.